A new local variety of Crepidomanes minutum (Hymenophyllaceae) in the Mascarene Archipelago (Indian Ocean) and a new record for Mauritius - Pynee, Kersley; Hennequin, Sabine; Echternacht, Livia; Dubuisson, Jean-Yves (Phytotaxa, 2012)
Crepidomanes minutum (Hymenophyllaceae) is here identified and recorded from Mauritius for the first time. The Mauritian specimens, in addition to those of La Réunion observed at low to middle elevations, are easily distinguished from populations observed outside the Mascarene Archipelago by their dwarfed size and rarity of the stipe proliferation that usually characterizes this species. We thus describe a new variety in this species for the Mascarene Islands.